2015
DOI: 10.3233/dev-140148
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Effects of Adolescent Volunteering on Secondary School Completion and Adult Volunteering

Abstract: This study explores the longitudinal effect of adolescent volunteering behaviour on young adult volunteering and the completion of secondary school. Utilising data from the Australian sample of the International Youth Development Study, frequency of volunteering in Grade 9 (mean age = 15 years) and in young adulthood (mean age = 21 years), and completion of secondary school were measured. Mixed effect logistic regression analyses revealed that adolescent volunteering was associated with an increased likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…It then follows that prior behaviours and attitudes are the most significant predictors of present or future behaviour. For example, Moorfoot, Leung, Toumbourou, and Catalano () found that young adolescents who are volunteering in their early teens are more likely to volunteer when they become young adults.…”
Section: Volunteer Withdrawalmentioning
confidence: 99%
“…It then follows that prior behaviours and attitudes are the most significant predictors of present or future behaviour. For example, Moorfoot, Leung, Toumbourou, and Catalano () found that young adolescents who are volunteering in their early teens are more likely to volunteer when they become young adults.…”
Section: Volunteer Withdrawalmentioning
confidence: 99%
“…Research has also shown a consistent link between adolescent community service and volunteering later in life (Kim and Morg€ ul, 2017;Moorfoot et al, 2015;see Youniss et al, 1997, for review). For example, Moorfoot et al's (2015) longitudinal work showed that volunteering in ninth grade was associated with volunteerism during early adulthood, even after controlling for family SES and adolescent adjustment.…”
Section: Benefits Of Community Servicementioning
confidence: 97%
“…Further, recent longitudinal work has shown associations between community service during adolescence and greater educational attainment. For example, Moorfoot et al (2015) found that volunteering in ninth grade was associated with high school completion, even after controlling for family socioeconomic status (SES) and individual characteristics. Further, this association is maintained, whether or not the community service is mandated, as Kim and Morg€ ul (2017) found that both required and voluntary service were associated with greater educational attainment and higher earnings in adulthood.…”
Section: Benefits Of Community Servicementioning
confidence: 99%
“…Although investigations have studied purpose and altruism/volunteerism in the youth (e.g., Moorfoot et al, 2015;Abramoski et al, 2018), few have examined the role that these play in identity development within an athletic context (Houltberg et al, 2018). The current study qualitatively investigates the nature of purpose and identity work in a sample of youths training and participating in full-and half-marathons through a non-profit faith-based program supporting humanitarian efforts in different countries on the African continent.…”
Section: Current Studymentioning
confidence: 98%
“…For example, a study of 9,471 adolescents found significant positive associations between volunteering and subsequent income and education level 12 years later (Ballard et al, 2018). Another study found that adolescents who volunteered in ninth grade were more likely to graduate high school, even after accounting for family socioeconomic status and adolescent school adjustment (Moorfoot et al, 2015). There is also evidence that altruism and volunteerism affect health; one study found that the adolescents who volunteered at a peer mentoring program had significantly lowered interleukin (IL)-6 levels (cells that are released due to infection, disease, or tissue injuries), lower cholesterol levels, and lower body mass index (BMI) levels compared with adolescents in the control group who did not volunteer (Schreier et al, 2013).…”
Section: Youth Altruism and Volunteerismmentioning
confidence: 99%